Systematic synthetic phonics as the most updated and useful teaching strategy that teachers must use for building up reading skills to first grade students at San Francisco de Asis School - Arcia, Kiara; Atencio, Xenia (David, Panamá : UDELAS, 2014)
Phonics is a method of teaching children how spoken words are composed of sounds called 'phonemes' and how the letters in words correspond to those phonemes. The process of reading involves decoding or 'breaking' words into separate phonemes, so that meaning can be gained. On the other hand, the process of spelling requires the writer to identify all the phonemes in a word and then use their knowledge of the phonemic code to write or 'make' the word.
TABLE OF CONTENTS CHART INDEX GRAPHIC INDEX INTRODUCTION CHAPTER I: ANTEDENTS AND STATEMENT OF THE PROBLEM 1.1. Antecedents 1.1.1. Teaching reading methods antecedents 1.2. Statement of the problem 1.3. Objetives 1.3.1. General Objetive 1.3.2. Specific Objetives 1.4. Justification 1.5. Scope and delimitation 1.6. Limitations CHAPTER II: THEORETICAL FRAMEWORK 2.1. Skill learners require for successful reading 2.1.1. Vocabulary knowledge 2.1.2. Phonological awareness 2.1.3. Orthographic awarebness 2.2. How the children learn to recognize the printed word 2.3. Types of reading instructions 2.3.1. Whole language approach 2.3.2. Whole word approach 2.3.3. Phonics based approach 2.3.3.1. Analytic phonic 2.3.3.2. Syntetic phonics 2.3.3.2.1. Teaching using the synthetic phonic CHAPTER III: METHODOLOGICAL ASPECTS 3.1. Type of research 3.1.1. Quantitative research 3.1.2. Demographic research 3.1.3. Descriptive research 3.2. Information sources 3.2.1. Material sources of information 3.2.2. Human sources of information 3.3. Subjects 3.3.1. Students 3.3.2. The teachers 3.4. Variable system (conceptual and operational definition) 3.4.1. Variable 1. Synthetic phonics 3.4.2.1. Conceptual definition 3.4.2.2. Operational definition 3.4.2. Variable 2. Reading process 3.4.2.1. Conceptual definition 3.4.2.2. Operational definition 3.5. Desription of data collection instruments 3.5.1. Observation checklist 3.5.2. Open ended survey 3.5.3. English reading proficiency test 3.6. Treatment of the information CHAPTER IV: ANALYSIS AND RESULTS 4. Descriptive analysis 4.1. Chart to analyze the results of the pre-test 4.1.1. Graphic of the pretest 4.2. Chart to analyze the interview for teachers 4.2.1. Item 1: The techers teach reading everyday 4.2.2. Item 2: The methodology used by teachers 4.2.3. Item 3: The most important aspect when teaching reading 4.2.4. Item 4: The suyccess in the teaching of reading 4.2.5. Item 5: Familiarity with the synthetic phonics strategy 4.3. Chart to analyze the teachers' classes' development from the observable checklist 4.3.1. Item 1: Showing the pronunciation of the whole word 4.3.2. The teacher showed the students how to pronounce the graphemes (phonemes of words) 4.3.3. Item 3: Repetition of the whole words by the students 4.3.4. Teaching the pronunciation of isolated phonemes 4.3.5. Item 5: The teacher taught reading 4.4. Chart to analyze the students' development in the english reading class 4.4.1. Item 1: The students read along with the teacher 4.4.2. Item 2: The accurateness of words pronunciation 4.4.3. Item 3: Students read vocabulary from their books 4.4.4. Item 4: The students are able to read already recognized works, but unable to read new ones 4.4.5. Item 5: Students seem to be comfortable and motivated and motivated when learning to read in English 4.5. Chart to analize the results of the post-test 4.5.1. Graphic of the post-test CONCLUSIONS RECOMENDATIONS BIBLIOGRAPHY ANNEX
Incluye TABLE OF CONTENTS
Documento presentado para optar por el título de Licenciatura en Docencia en Inglés.
Incluye Bibliografía
No se presta a domicilio.
No se saca fotocopias.
Keywords: ENGLISH -- TESIS DE LICENCIATURA; INGLÉS -- TESIS DE LICENCIATURA; PHONETICS -- TESIS DE LICENCIATURA; FONETICA; FONOLOGÍA -- PRONUNCIACIÓN -- TESIS; LICENCIATURA EN DOCENCIA EN INGLÉS - TESIS; SAN FRANCISCO DE ASIS SCHOOL; READING SKILLS - STUDENTS; TEACHING STRATEGY